Financial Sustainability as a Catalyst for SDG Implementation in Higher Education: Evidence from Tribhuvan University - Shrestha, Rupa (Janaprakash Journal of Multidisciplinary Research, 2025)
This study examines the role of financial sustainability and public investment in embedding SDG 4.7 at Tribhuvan University, Nepal’s largest public university. This study is grounded in a social constructivist paradigm, a qualitative multi-method design was employed, including semi-structured interviews with university leaders, systematic review of policy documents, and analysis of institutional budgets over a ten-year period. Findings indicate that despite formal alignment with SDGs and supportive national policies, reliance on recurrent government grants constrains curriculum reform, sustainability research, and education for sustainable development initiatives. Project-based and performance-linked funding partially addresses these limitations, yet fragmented financing and limited institutional autonomy hinder systematic integration. The study concludes that financial sustainability plays a decisive role in integrating SDG 4.7 within academic, governance, and sustainability practices. However, SDG 4.7 remains weakly embedded due to limited program-oriented public investment and a predominance of administrative spending, which constrains effective SDG policy integration at the institutional level. The study contributed the evidence-based guidance for policymakers, UGC, and national SDG planners. Furthermore, the study encourages future research on the role of public investment policy in shaping integrated university financial systems for sustainable higher education in Nepal.